Why sentence? Comparing the views of jurors, judges and the legislature on the purposes of sentencing in Victoria, Australia - Warner, Kate Eleonore (Criminology & criminal justice, 2019)
In recent times, parliaments have introduced legislation directing judges to take defined purposes into account when sentencing. At the same time, judges and politicians also acknowledge that sentencing should vindicate the values of the community. This article compares the views on the purposes of sentencing of three major participants in the criminal justice system: legislators who pass sentencing statutes, judges who impose and justify sentences and jurors who represent the community. A total of 987 Australian jurors in the Victorian Jury Sentencing Study (2013-2015) were asked to sentence the offender in their trial and to choose the purpose that best justified the sentence. The judges’ sentencing remarks were coded and the results were compared with the jurors’ surveys. The research shows that, in this jurisdiction, the views of the judges, the jurors and the legislators are not always well aligned. Judges relied on general deterrence much more than jurors and jurors selected incapacitation as the primary purpose in only about a fifth of ‘serious offender’ cases where parliament has provided that community protection must be the principal purpose.